Spectrum of the quadratic eigenparameter dependent discrete Dirac equations - Koprubasi, Turhan (Springer Science and Business Media LLC, 2014)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: discrete spectrum; Algebra and Number Theory; Applied Mathematics; Particular ordinary differential operators (Dirac, one-dimensional Schrödinger, etc.); discrete Dirac equations; spectral analysis; spectral singularities; Eigenvalue problems for linear operators; eigenparameter; Spectrum, resolvent; Analysis; 16. Peace & justice; 3. Good health